2018
DOI: 10.1021/acssuschemeng.8b04844
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the PbS Dendritic Nanostructure Recovered from a Spent Lead-Acid Battery via an Integrated Vacuum Chlorinating and Hydrothermal Process

Abstract: An integrated two-step process, comprising vacuum chlorinating and hydrothermal synthesis, is developed for direct recovery of the three-dimensional lead sulfide (PbS) dendrite product from the lead paste of spent lead-acid batteries (LABs). In the vacuum chlorinating stage, different lead components, comprising lead (Pb), lead oxide (PbO), lead dioxide (PbO2), and lead sulfate (PbSO4) in the spent lead paste, are all converted into volatile lead chloride (PbCl2) with calcium chloride (CaCl2) as the environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In previous studies, researchers have tried to convert SLP into lead products such as metallic lead, organic lead compounds, , lead oxide, , lead chloride, , lead iodide, and lead sulfide. Yang et al used a combination of wet desulfurization and a roasting process to prepare lead oxide products . Liu et al reported on a vacuum chlorination process with calcium chloride as a reagent to successfully produce high-purity lead chloride products .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers have tried to convert SLP into lead products such as metallic lead, organic lead compounds, , lead oxide, , lead chloride, , lead iodide, and lead sulfide. Yang et al used a combination of wet desulfurization and a roasting process to prepare lead oxide products . Liu et al reported on a vacuum chlorination process with calcium chloride as a reagent to successfully produce high-purity lead chloride products .…”
Section: Introductionmentioning
confidence: 99%
“…21 Thus, chlorine shows promising potential applications in heavy metal recovery and metallurgical industry. 22,23 However, the existing chlorination methods display disadvantages, such as a low extraction rate and high energy consumption. Besides, the chlorination technique has never been applied to the recovery of Cr.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, spent lead paste has been converted into various lead products, such as pure lead, , lead oxide, lead citrate, , and lead chloride . Lead sulfide (PbS) is an important high-value product of the lead family because of its value in semiconductors and photoelectrical materials, and it needs to be given full attention by researchers investigating the recycling of spent lead paste. Regrettably, few efforts along these lines have been attempted.…”
Section: Introductionmentioning
confidence: 99%